1987
DOI: 10.1007/bf01885108
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fibers in the preparation of the bowel for diagnostic barium enema

Abstract: The effect on colon cleanness of adding dietary fiber or placebo to a standard bowel preparation scheme before diagnostic barium enemas was tested in a randomized, double-blind study including 120 consecutive outpatients admitted for diagnostic barium enemas. Colon cleanness was scored as satisfactory, intermediate, or unsatisfactory. No case of unsatisfactory cleansing appeared in the group given fiber. Mean score was slightly better in the fiber group but the difference was not statistically significant. Die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…In some studies [12,14,32] a low-fiber diet or a low-residue diet kit was prescribed for CT colonographic bowel preparation, whereas in others a specific diet prescription was not used [8,11,31]. In addition, a few studies [19,21,33] have been conducted with low-fiber or low-residue diets in bowel preparation for double contrast barium enema. One half of these studies showed no effect of ingestion of a specific diet on colon cleanness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some studies [12,14,32] a low-fiber diet or a low-residue diet kit was prescribed for CT colonographic bowel preparation, whereas in others a specific diet prescription was not used [8,11,31]. In addition, a few studies [19,21,33] have been conducted with low-fiber or low-residue diets in bowel preparation for double contrast barium enema. One half of these studies showed no effect of ingestion of a specific diet on colon cleanness.…”
Section: Discussionmentioning
confidence: 99%
“…The issue of bowel preparation has been addressed in studies of the use of a low-fiber and low-residue diets for barium enema [19][20][21][22][23]. Some of these studies showed no benefit from the use of a prescribed diet with respect to amount of fecal residue or diagnostic quality [19][20][21]. Other studies [22,23], however, showed that the amount of fecal residue diminishes and image quality improves with the use of a WEB This is a Web exclusive article.…”
mentioning
confidence: 99%
“…By doing so, high degrees of cleanness of the colon have been achieved in spite of diverticula disease and advanced age (3). This study has shown that fibre treatment as a supplement to normal diet does not need to be interrupted in order to obtain this high degree of cleanness (4). This result indicates more simple management of patients already under treatment with bulk and fibre (2), and, for instance, of vegetarians.…”
Section: Discussionmentioning
confidence: 67%
“…found that Picolax with a 36 h LRD and Picolax with 36 h starvation were equally effe~tive.~ In contrast to these papers, a randomized study of 120 patients by Hellstrom and Brolin found that the addition of a 5-day high-fibre preparation to a bisacodyl and cleansing-enema regimen did not affect colon cleansing. 6 The same authors suggested that fibre may have a beneficial effect, more pronounced in patients with constipation, and that the discontinuation of dietary fibre medication prior to a BE was not justified. In our study, the addition of a 3-day LRD to Picolax conferred no benefit.…”
Section: Discussionmentioning
confidence: 99%
“…At 17.00 h a packet of Ween-Prep (polyethylene glycol 3350 59 g, sodium sulphate 5.7 g, sodium bicarbonate 1.7 g, sodium chloride 1.59, potassium chloride 0.7g, aspartame 0.05g) was dissolved in 1 L of cold water, and a glassful taken every 15 min. This was repeated until all four packets had been taken over [4][5][6] h. Only clear fluids were allowed after this, and on Day 6, prior to the BE.…”
Section: Methodsmentioning
confidence: 99%